Characteristics of Pancreaticoduodenal Resection on Periampullary Tumor Cases by Jakarta Tertiary Hospital Team: Three Decade Report - Toar JM Lalisang; Yarman Mazni; Yefta Moenadjad; Sahat Matondang (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Background: There were only few publications related to pancreaticoduodenal resection (PDR) /Whipple procedure in Indonesia in the past decade.Method:  Retrospectively report of  the characteristics and outcomes of PDR performed by Cipto Mangunkusumo Hospital surgical team from 1993 to 2017 were collected.Results: PDR were performed in 213 patients, with a mean age of 50.6 years and 54.4% patients were females. Predominant preoperative clinical findings were jaundice (68.9%) and mild hypoalbuminemia (69.9%). Biliary decompression was performed in 112 (52.6%) subjects. Average surgical waiting time was 3.5 months. While PDR were performed in 84 (39.5%) subjects, pyloric preserving pancreaticoduodenal technique was predominated in 128 (59.8) and predominated,  especially during the latter years. Fifteen (9.0%) cases were benign. Thirty-one (14.6%) subjects underwent relaparotomy, 16 (51.6%) of whom died post-operatively. Overall operative mortality decreased from 16.9% to 5.5% in 2016, while resection rate generally increased over time, ranging from 2 - 21/year. Less than 10% of subjects survived for 5 years, while 20% survived for 24 months.  Overall morbidity was 65.1% in 177 survivors, with surgical site infection in 52.5%, pancreatic fistula in 24.2%, and post-pancreatectomy haemorrhage (PPH) as a fatal postoperative complication in 19 (8.9%) cases. Patients who died within 30 days postoperatively had significantly more relaparotomies and PPH (p 0.001).Conclusion: Prolonged jaundice and mild hypoalbuminemia are dominant characteristics in our Indonesian PDR subjects. Cipto Mangunkusumo Hospital is a high-volume PDR centre and world class hospital. Mortality rates decreased with the increasing resection rates. Relaparotomy and PPH are predictors of poor outcome.